Omental Patching and Purse-String Endosuture Closure after Endoscopic Full-Thickness Resection in Patients with Gastric Gastrointestinal Stromal Tumors - Faisal Inayat; Aysha Aslam; Mathew D. Grunwald; Qulsoom Hussain; Abu Hurairah; Shahzad Iqbal (Korean Society of Gastrointestinal Endoscopy, 2019)
Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal tumors of the gastrointestinal tract, primarily arising from the stomach. With the widespread utilization of and technical advancements in endoscopy, gastric GISTs are being increasingly detected at an early stage, enabling complete endoscopic resection. Endoscopic full-thickness resection (EFTR) is an advanced technique that has been recognized as a treatment tool for neoplasms in the digestive tract in selected patients. Although a number of methods are available, closing large iatrogenic defects after EFTR can be a concern in clinical practice. If this potential problem is appropriately solved, patients with gastric GISTs would be suitable candidates for resection utilizing this technique. To our knowledge, this is the first study to propose omental patching and purse-string endosuture closure following EFTR as a feasible endoscopic option in patients with gastric GISTs.